Experimental investigation on failure modes of RECC slab-column connections under concentric gravity loading. (1st March 2021) - Ye, Binbin; Pan, Peng; Xiao, Genqi; Zhang, Yaoting; He, Zhizhou
Highlights: RECC slab-column connections showed flexural-triggered or punching shear failure. Flexural-triggered failure modes has ductility ratios between 1.63 and 6.4. Ductile failure modes can be achieved by adjusting reinforcement ratio. Ultimate strength of RECC specimens were estimated and the errors are within 15%. Abstract: RC flat-slab is widely regarded as one of the mainstream design solutions in commercial engineering projects due to its flexibility and the characteristic of maximization of floor-to-floor height. However, RC slab-column connections are vulnerable to punching shear failure due to the brittle tensile behavior of standard concrete. Engineered cementitious composites (ECC) have greater ductility than standard concrete which makes it ideal for slab-column connections. In this study, five RECC slab-column connections, which have different reinforcement ratios (ρ) and span ratios (λ), were tested under concentric gravity load to investigate their failure behaviors. Reinforcement ratios of ρ = 0.2%, 0.6%, 1.4% and 2.3%, as well as span ratios of λ = 8.4 and 5.7 were considered. Flexural strengths V flex of specimens were estimated based on yield-line theory, and punching shear strengths V pun of specimens were estimated by empirical formulas of ACI and JSCE codes. The main conclusions obtained in this study are as follows: (1) At a fixed span ratio of λ = 8.4, specimen with ρ = 0.2% experienced premature flexural failure after yielding reinforcement, while specimens with ρ = 0.6% and 1.4% both experienced flexural-triggered punching shear failure. In addition, premature punching shear failure occurred in ρ = 2.3% specimen. For specimens with λ = 5.7 and ρ = 1.4%, the flexural-triggered punching shear failure was also exhibited. (2) The ductility ratios of specimens with flexural-triggered failure modes (i.e. premature flexural failure and flexural-triggered punching shear failure) varied from 1.63 to 6.4. Premature flexural failure has the lowest ductility ratio of 1.63 amongst the flexural-triggered failure modes. Additionally, punching shear failure has the lowest ductility ratio of all the failure modes, which is close to 1.0. (3) The lesser of V flex and V pun was adopted as the estimated ultimate load, the errors between the test results and the estimated values are within 15%. (4) Flexural-triggered failure modes or strong-shear-weak-bending design can be achieved by making V pun > V flex through restricting the maximum reinforcement ratio. Premature flexural failure can be avoided by limiting the minimum reinforcement ratio.